Adherence to physical activity and quality of life in individuals after bariatric surgery (Revista Contexto & Saúde, 2023)
Bariatric surgery is surgery on the digestive system that aims to reduce body weight by decreasing gastric capacity and consequently reducing food intake. Not only weight loss is expected, but changes in health parameters and quality of life. The aim of the study was to investigate the adherence to physical exercise and the quality of life of individuals undergoing bariatric surgery. A cross-sectional, analytical and quantitative study. A sociodemographic/health conditions questionnaire, a quality of life questionnaire (Whoqol Bref) and a physical exercise adherence questionnaire (EARS-Br) were applied. The sample consisted of 76 people (60 women), 38 (50%) between the age groups of 40 to 60 years, 57 (75%) completed higher education and the family income of the majority was from 1 to 3 minimum wages (39/51.3%). Most participants were overweight (32/43.2%) and were not smokers (56/73.7%), while 34 (44.7%) used alcoholic beverages. Most did not exercise before surgery (53/69.7%). After the bariatric surgery, the quality of life was very good and the practice of physical activity improved, but 48 (63.2%) did not adhere to the routine satisfactorily. Lack of time was the main factor for non-adherence. It is concluded that adherence to physical activity was not included as a lifestyle, with no correlation with adherence to physical exercise and quality of life in the evaluated sample.